Modeling eco-efficiency changes of heterogeneous firms with an application in power plants / Behrouz Arabi - Arabi, Behrouz (2013)
The objective of power industry restructuring worldwide has been to enhance efficiency, hence providing an increased focus on efficiency measurement in power industries. Power generation which plays a key role in the power industry accounts for a noticeable share of emission generation amongst all power industry sectors. This would be costly not only for the sector itself, but also for the entire economy. Thus, the ecological impact of power generation should not be neglected in efficiency measurement. In addition, the non-homogeneous nature of power generation technologies has always been a barrier to drawing a complete picture of power generation industry efficiency or to compare the relative efficiency of different power plant technologies using methodologies such as Data Envelopment Analysis (DEA). In view of the above, this research aims for introducing a more comprehensive DEA method to measure the ecological efficiency or eco-efficiency trend of heterogeneous power plants during an eight-year period of power industry restructuring in Iran using a popular measure known as the Malmquist-Luenberger index (MLI). Toward this aim, the study tackles a prevalent infeasibility problem which occurs when the traditional Directional Distance Function (DDF) or slack-based DEA models are adopted to measure MLI. This study introduces an algorithm accompanied by a slack-based model to tackle the infeasibility problem. In addition, to represent thermodynamic realities of mechanical systems more accurately, the study incorporates the Materials Balanced Principle (MBP) requirement in the measurement of efficiency by adopting a slack-based DEA model. As fuel rotation is an approach to generate the same amount of energy with less emission or cost, a fuel control constraint has been introduced to all MBP-enabled DEA models. Furthermore, to measure the trend of ecological efficiency during the eight-year period of restructuring across the Iranian power industry, in addition to conventional technical PhD Thesis Modeling Eco-efficiency Changes of Heterogeneous Firms with an Application in Power Plants efficiency measures, some DEA models are also introduced and adopted to identify efficient power plants based on a number of factors; namely, less fuel consumption, combustion of less polluting fuel types, and incorporating emission factors. In addition, to see the effects of restructuring on the efficiency measures, rather than on the factors conventionally used for eco-efficiency and cost efficiency measurement, values of inputs and outputs are calculated using a new set of rules and regulations affected by restructuring. Due to the non-homogenous nature of different power plant technologies, in the studies undertaken so far, efficiency and eco-efficiency measurements have been carried out within the homogenous power plant categories. However, in order to provide more comprehensive information for future planning and budgeting and to draw a complete picture of the performance delivered by heterogeneous power plants, this study introduces models which can handle heterogeneous firms and are deployed to measure cost and allocative efficiency in addition to the eco-efficiency of power plants. Results reveal improvements in the eco-efficiency, cost efficiency and allocative efficiency of power plants during the restructuring period. It is also shown that although hydro power plants may look more eco-efficient, in Iran, the combined-cycle ones have been more allocatively efficient than those of other power generation technologies. Furthermore, results have exhibited that gas is the most cost-efficient, but less allocatively efficient technology in Iran.